Sem'ia i shkola: formirovanie vzaimodeistviia v polietnicheskoi srede - Strukova E. S., Shaulov V. I. (Competence approach in education: trends and challenges)
This article reveals the mechanism of interaction and the formation of the child in the multiethnic environment class. The mechanism of the relationship of the family, as a factor in the development of tolerance in the child and the school as a liaison between the family.
Keywords: Семья; школа; толерантность; многонациональная среда; family; School; multicultural environment; tolerance